Inverse remodelling of K2P3.1 K+ channel expression and action potential duration in left ventricular dysfunction and atrial fibrillation: implications for patient-specific antiarrhythmic drug therapy. (5th January 2017) - Schmidt, Constanze; Wiedmann, Felix; Zhou, Xiao-Bo; Heijman, Jordi; Voigt, Niels; Ratte, Antonius; Lang, Siegfried; Kallenberger, Stefan M.; Campana, Chiara; Weymann, Alexander; De Simone, Raffaele; Szabo, Gabor; et al.
Abstract: Aims: Atrial fibrillation (AF) prevalence increases with advanced stages of left ventricular (LV) dysfunction. Remote proarrhythmic effects of ventricular dysfunction on atrial electrophysiology remain incompletely understood. We hypothesized that repolarizing K2P 3.1 K +  channels, previously implicated in AF pathophysiology, may contribute to shaping the atrial action potential (AP), forming a specific electrical substrate with LV dysfunction that might represent a target for personalized antiarrhythmic therapy. Methods and results: A total of 175 patients exhibiting different stages of LV dysfunction were included. Ion channel expression was quantified by real-time polymerase chain reaction and Western blot. Membrane currents and APs were recorded from atrial cardiomyocytes using the patch-clamp technique. Severely reduced LV function was associated with decreased atrial K2P 3.1 expression in sinus rhythm patients. In contrast, chronic (c)AF resulted in increased K2P 3.1 levels, but paroxysmal (p)AF was not linked to significant K2P 3.1 remodelling. LV dysfunction-related suppression of K2P 3.1 currents prolonged atrial AP duration (APD) compared with patients with preserved LV function. In individuals with concomitant LV dysfunction and cAF, APD was determined by LV dysfunction-associated prolongation and by cAF-dependent shortening, respectively, consistent with changes in K2P 3.1 abundance. K2P 3.1 inhibition attenuated APD shortening in cAF patients irrespective of LV function, whereas in pAF subjects with severely reduced LV function, K2P 3.1 blockade resulted in disproportionately high APD prolongation. Conclusion: LV dysfunction is associated with reduction of atrial K2P 3.1 channel expression, while cAF leads to increased K2P 3.1 abundance. Differential remodelling of K2P 3.1 and APD provides a basis for patient-tailored antiarrhythmic strategies.